Psychological Stress and Functional Endometrial Disorders: Update of Mechanism Insights - Wu, Jin-xiang; Lin, Shu; Kong, Shuang-bo (Frontiers in Endocrinology, 2021)
The human endometrium plays a vital role in providing site for the embryo implantation and maintaining the normal development and survival of the embryo. Recent studies have shown that psychological stress is a common factor for the occurrence of unexplained reproductive disorders. Nonreceptive endometrium and disturbed maternal-fetal interaction at early pregnancy might lead to infertility due to repeated embryo implantation failure, recurrent spontaneous abortion, or late pregnancy complications, thereby affecting the quality of life as well as the psychological status of the affected individuals. Additionally, psychological stress might also adversely affect female reproductive health. In recent years, several basic and clinical studies have tried to investigate the harm caused by psychological stress to reproductive health; however, the mechanism is still unclear. Here, we review the relationship between psychological stress and endometrial dysfunction, and its consequent effects on female infertility, aiming to provide new insights for clinical therapeutic interventions in the future.